Biochemical and histopathological studies of the liver of wistar rats fed Spirulina strain LEB-18 in micrometric and nanometric size - Machado, Adriana Rodrigues (2021)
The aim of the study was to evaluate the biochemical and histopathological responses of rats fed for 15 days on diets containing Spirulina strain LEB 18 in micrometer size (Sm) and nanometer (Sn), an aproteic diet (A) and a control diet (C) containing casein. 24 recently weaned (21 days) female rats of the Wistar/UFPEL strain were used. The analyses carried out were: lipids in the diets, (excreta) feces  and liver, and calculation of lipid digestibility, serum biochemical determinations of total cholesterol and fractions (LDL, HDL and VLDL) and triacylglycerols and blood glucose, and histopathological evaluation of the livers. The diets containing Spirulina LEB 18 in the micro and nanometer sizes did not alter biochemical parameters (total and fractions cholesterol, triacylglycerols and glucose) of Wistar rats in growth. Physiological and biochemical data from rats subjected to diet (A) indicate an impairment in the metabolism of lipids, due to the absence of protein in it, which directly reflected in hepatic lesions that were very heterogeneous regarding the pattern and intensity in relation to the other diets, and may be due to lipid deposition more evidenced in an aproteic diet, probably caused by protein deficiency and therefore the decline in production and export of lipoproteins by the liver.